The mercury species and their association with carbonaceous compositions, bromine and iodine in PM2.5 in Shanghai. (March 2016) - Duan, Lian; Xiu, Guangli; Feng, Ling; Cheng, Na; Wang, Chenggang
Abstract: PM2.5 samples were collected in south Shanghai from November 2013 to October 2014. The species of particulate bounded mercury (PBM), including hydrochloric soluble particle-phase mercury (HPM), element soluble particle-phase mercury (EPM) and residual soluble particle-phase mercury (RPM), were determined in PM2.5 . The chemical composition of PM2.5 including organic carbon (OC) and elemental carbon (EC), total bromine and iodine were also analyzed. The results showed that the annual average concentration of PBM was 0.30 ± 0.31 ng m −3 and 0.34 ± 0.32 ng m −3 in winter, 0.31 ± 0.19 ng m −3 in spring, 0.30 ± 0.45 ng m −3 in fall and 0.28 ± 0.17 ng m −3 in summer. HPM took the highest fraction 51.2% in PBM, followed by RPM 27.7% and EPM 21.1%. EC positively correlated to particle mercury, especially in winter (r = 0.70), the same for OC in winter (r = 0.72), which indicated that the carbonaceous composition may affect the transformation of Hg in the atmosphere. Mercury species showed different correlations with bromine and iodine in the four seasons. The strongest correlation between bromine, iodine and mercury was found in spring and fall, respectively. Bromine showed the stronger correlation with total mercury and speciated particle mercury than iodine. In addition, the days were classified into haze and non-haze days based on the visibility and relative humidity, while the ratio of HPM in haze days was much higher than that in non-haze days. EC strongly correlated with PBM during haze and non-haze days while OC only positively correlated with PBM in non-haze days, this may indicate that the different carbonaceous part may affect PBM differently. Highlights: The seasonal patterns of PBM and particle speciated Hg are summarized. Particle Br has stronger correlation with HPM than I especially in haze days. EC positively correlated to particle mercury, especially in winter, the same for OC in winter.